High-pressure liquid chromatography (HPLC) pigment concentration data and flow-cytometry picophytoplankton abundance and fluorescence data from depth-resolved CTD profiles at extquotesingleBiomass stations extquotesingle during RV Tangaroa expedition TAN1702 - Andrés Gutiérrez-Rodríguez; Mikel Latasa; Karl Safi; Matt Pinkerton; Scott D Nodder (PANGAEA, 2023)
Here we present data of phytoplankton pigment and flow cytometry (FCM) depth-resolved data collected from the water column (0-100 m) during TAN1702 voyage (March-April 2017) in subantarctic waters across the Campbell Plateau region southeast of New Zealand on board of the RV Tangaroa.
In: Gutiérrez-Rodríguez, A et al. (2023): Phytoplankton taxon-specific growth and microzooplankton grazing rates in subantarctic HNLC waters on and off Campbell Plateau southeast of New Zealand during austral autumn [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.958525